2016
DOI: 10.1097/iae.0000000000001328
|View full text |Cite
|
Sign up to set email alerts
|

Toward Quantitative Optical Coherence Tomography Angiography

Abstract: Structured Abstract PURPOSE Currently available optical coherence tomography (OCT) angiography (OCTA) systems provide information about blood flux, but limited information about blood flow speed. We develop a method for mapping the previously proposed variable interscan time analysis (VISTA) algorithm into a color display that encodes relative blood flow speed. METHODS OCTA was performed with a 1050 nm, 400 kHz A-scan rate, swept source OCT system using a 5 repeated B-scan protocol. VISTA was used to comput… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
59
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 117 publications
(59 citation statements)
references
References 41 publications
0
59
0
Order By: Relevance
“…Also, shorter wavelengths are more prone to scattering and attenuation; thus, they penetrate into tissue less than the longer wavelengths used in the SS-OCT devices. SS-OCT devices typically use wavelengths above 1000-nm and operate at speeds equal to or greater than 100-kHz (Drexler and Fujimoto 2008, Ploner, Moult et al 2016). …”
Section: Principles Of Optical Coherence Tomography Angiographymentioning
confidence: 99%
See 2 more Smart Citations
“…Also, shorter wavelengths are more prone to scattering and attenuation; thus, they penetrate into tissue less than the longer wavelengths used in the SS-OCT devices. SS-OCT devices typically use wavelengths above 1000-nm and operate at speeds equal to or greater than 100-kHz (Drexler and Fujimoto 2008, Ploner, Moult et al 2016). …”
Section: Principles Of Optical Coherence Tomography Angiographymentioning
confidence: 99%
“…A variable interscan time analysis (VISTA) method was proposed to investigate the effect of different interscan times on vascular changes in the choriocapillaris of patients with nonexudative AMD and geographic atrophy. The VISTA method calculated the flow signals between sequential OCT B-scans (1 and 2, 2 and 3, 3 and 4, and 4 and 5, where interscan time was approximately 1.5-ms) and between every two B-scans (1 and 3, 2 and 4, and 3 and 5, where interscan time was approximately 3-ms) respectively (Ploner, Moult et al 2016). Their results demonstrated that VISTA was able to shift the range of the detectable flow speeds.…”
Section: Principles Of Optical Coherence Tomography Angiographymentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, to describe the functional state of the microcirculation, it would be essential to determine the blood flow velocity in OCTA images of the sublingual microcirculation (as a measure of convective flow) 26 , which was not possible with the device used. However, recent experimental and clinical studies describe an automatic measurement of blood flow velocity in OCTA images of the retina [42][43][44] . Third, in OCTA images of the retina and choroid, single layers are automatically identified and flow density for the respective layer calculated.…”
mentioning
confidence: 99%
“…To obtain flow signal, OCTA algorithms [1,3,[18][19][20] rely on mathematical operations that quantify variations in the amplitude and/or the phase of optical coherence tomography (OCT) signal between at least two consecutive B-scans acquired at the same raster position. However, since the interscan time cannot be extremely small without affecting sensitivity to slow-speed blood flow [21,22], OCTA of the retina is sensitive to involuntary eye motion between B-scans.…”
Section: Introductionmentioning
confidence: 99%